2016
DOI: 10.12688/f1000research.7218.1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative sleep apnea: a real problem or did we invent a new disease?

Abstract: Depending on the subpopulation, obstructive sleep apnea (OSA) can affect more than 75% of surgical patients. An increasing body of evidence supports the association between OSA  and perioperative complications, but some data indicate important perioperative outcomes do not differ between patients with and without OSA. In this review we will provide an overview of the pathophysiology of sleep apnea and the risk factors for perioperative complications related to sleep apnea. We also discuss a clinical algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 174 publications
0
10
0
Order By: Relevance
“…[ 17 18 19 20 ] The conducted study showed that pain was a unique significant postoperative complication, which was proved by the studies of other scientists. [ 21 22 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 19 20 ] The conducted study showed that pain was a unique significant postoperative complication, which was proved by the studies of other scientists. [ 21 22 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Keeping a patient as upright as possible during induction may help optimize mask ventilation and also help during extubation. This approach may prevent atelectasis, which may be especially important in patients with OSA 24, 25 .…”
Section: Recommendations For Patient Managementmentioning
confidence: 99%
“…An additional hurdle includes post-operative pain management, as OSA patients demonstrate decreased pain tolerance post-operatively. This decreased pain tolerance, combined with baseline hypopnea and increased sensitivity to respiratory depression by opioids, makes their post-operative course especially dangerous and complicated [8][9]. Intravenous (IV) opioids are the most commonly used drugs for pain control in the postanesthesia care unit (PACU).…”
Section: Introductionmentioning
confidence: 99%